Pollen-mediated gene flow from a commercial potato cultivar to the wild relative S. chacoense bitter under experimental field conditions in argentina - Capurro, Mauricio Antonio (2013)
The common potato, Solanum tuberosum ssp. tuberosum (tbr, 2n = 4x = 48; 4EBN), has many closely related wild tuber-bearing species. Around 28 to 35 of them spontaneously grow in Argentina overlapping, in some areas, with the crop and/or experimental transgenic potatoes. Although it is well proven that hybridization barriers in potatoes can be incomplete, information on gene flow between cultivated and wild germplasm is scarce. Thus, a gene flow field experiment with a circular array was set up in Balcarce, Argentina, in 2009, and evaluated over two seasons. The tetraploid tbr cultivar Huinkul MAG and one compatible cloned genotype of the related wild potato S. chacoense Bitter (chc, 2n = 2x = 24; 2EBN), which produced 2n eggs, were used, respectively, as pollen donor and receptor. Berries with hybrid seeds - as revealed by ploidy and RAPD profiles - were obtained in one season, at 30 m from the pollen donor. These results reinforce others previously obtained with the same pollen donor and a male sterile tbr cultivar in a similar array, pointing out to the need of increasing isolation distances in areas of overlap between cultivated and wild potato germplasm to prevent or minimize undesirable pollen-mediated gene flow. © 2013 The Authors.